Technologies of medical diagnosis and treatment of invasive candidiasis in children - S.O. Mokia-Serbina; S.О. Sheyko; V.I. Fesenko; T.М. Lytvynova; N.I. Zabolotnya; V.А. Shelevytska (Zdorovʹe Rebenka)
The advancement of intensive care and the widespread use of invasive procedures have led to an increase in candidiasis in both immunocompromised children and children without signs of immunodeficiency. Constant stress and psychological trauma associated with war lead to a weakening of the immune system and an increased risk of infections, including fungal ones. Invasive candidiasis in children does not have specific clinical signs. In turn, limited access to the necessary studies contributes to a delay in diagnosis and treatment. This work is a review of current recommendations and expert consensuses from a number of associations on the diagnosis, treatment and prevention of invasive candidiasis in children. The resources under study contain guidelines from the European Society of Clinical Microbiology and Infectious Diseases, the Infectious Diseases Society of America, the International Pediatric Network, the European Conference on Infections in Leukemia-6, the Australian Society for Infectious Diseases, statement of the American Thoracic Society on the diagnosis of fungal infections. When analyzing the sources, Scopus, PubMed, Google Scholar, Web of Science databases were used. The national standards of medical care “Rational use of antibacterial, antifungal drugs for therapeutic and prophylactic purposes”, “Standards of medical care. Invasive candidiasis in newborns” were also considered. The presented materials will increase the relevance of candidiasis problem in children in real modern conditions. Thorough monitoring of seriously ill children who are at risk of developing the disease will contribute to the early detection of candidiasis. A comprehensive approach to the diagnosis of candidiasis will provide convincing treatment results.